Effect of trabeculectomy on ocular blood flow. Issue 2 (21st January 2005) - Berisha, F; Schmetterer, K; Vass, C; Dallinger, S; Rainer, G; Findl, O; Kiss, B; Schmetterer, L
Abstract : Background/aim: Current evidence suggests that vascular insufficiencies in the optic nerve head play an important part in the pathogenesis of glaucomatous optic neuropathy. Trabeculectomy is the most common operative procedure for the treatment of medically uncontrolled glaucoma. This study was conducted to investigate whether trabeculectomy may improve ocular haemodynamics. Methods: 30 patients with primary open angle glaucoma about to undergo trabeculectomy were included in the study. Patients were evaluated before surgery and at 2 and 10 weeks after trabeculectomy. Optic nerve head blood flow (OnhBF) was assessed with scanning laser Doppler flowmetry. Fundus pulsation amplitude (FPA) measurements were obtained with laser interferometry. Results: Because of the decrease in intraocular pressure there was a significant increase in ocular perfusion pressure (OPP) following trabeculectomy (18.5% (SD 12.0%) and 19.0% (17.1%) at 2 and 10 weeks postoperatively; p <0.001). A significant increase in OnhBF was observed after trabeculectomy (11.6% (16.4%) and 16.2% (20.2%) for each postoperative visit, respectively; p <0.001). FPA was also significantly higher compared with baseline values (17.2% (17.3%) and 17.4% (16.3%), respectively; p <0.001). A significant association between the increase in OPP and the increase in OnhBF and FPA was observed 10 weeks after surgery ( r = 0.47; p = 0.009, and r = 0.50; p = 0.005, respectively). Conclusion: The results of this study suggest that trabeculectomy improves ocular blood flow in patients with chronic open angle glaucoma.